A HOLISTIC PRODUCTIVE ZAKAT GOVERNANCE MODEL BASED ON GOOD COMMUNITY ENGEGAMENT - Wasik , Abdul; Lilit Biati , Lilit; Irma Nur Hayati, Irma; Imron , Muhammad; Hidayatul Amri, Lutfi (FORPIM PTKIS ZONA TAPAL KUDA, 2025)
Productive zakat is a strategic instrument for transformative and long-term-oriented economic empowerment of the ummah. Its implementation demands governance that is grounded in transparency, participation, and sustainability. The Zakat Village of BAZNAS Bondowoso and the SDGs Village of BAZNAS Jember serve as examples of community-based zakat implementation. However, a systematic and contextual governance model is still needed to promote the transformation of mustahik into muzakki and to foster ISI-based qualities: intellectuality, spirituality, and integrity. This study aims to develop a holistic productive zakat governance model based on Good Community Engegament (GCG) as an effort to enhance the effectiveness of zakat distribution and the transformation of mustahik into muzakki. Through a qualitative approach and case studies in BAZNAS Bondowoso’s Zakat Village and BAZNAS Jember’s SDGs Village, this research explores five core pillars of GCG: participation, accountability, transparency, inclusiveness, and sustainability. The findings show that integrating GCG principles with a holistic productive zakat approach can create governance that is not only efficient and effective but also empowers the community spiritually, intellectually, and socially. This model offers a new policy formulation in zakat management that is not merely institutional-based but rooted in the strength of local communities.